Self-esteem dan regulasi emosi dalam pencegahan bullying pada anak usia sekolah dalam kerangka social emotional learning (SEL): Sebuah tinjauan literatur sistematis - Jehan, Reisha Zahra Syah; Rahayu, Rita; Ahmad, Ghulam (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Bullying is a form of repeated violence that seriously impacts adolescent mental health, with a global prevalence of approximately 30%. Self-esteem and emotion regulation act as risk and protective factors, while social emotional learning (SEL) approaches have potential as preventative strategies, but their integration remains limited. Purpose: To identify and evaluate the role of social emotional learning (SEL) in strengthening self-esteem and emotion regulation as a bullying prevention effort. Method: This was a systematic literature review, adhering to the PRISMA 2020 guidelines. Analysis used quantitative narrative synthesis and JBI quality assessment. A literature search was conducted through four databases: ScienceDirect, ERIC, Google Scholar, and PubMed. A total of 2,137 articles were identified, 79 duplicates were removed, and 1,872 were eliminated during initial screening. Of the 186 articles screened, 16 studies met the inclusion criteria. Results: Self-esteem and emotion regulation were significantly associated with bullying behavior. Self-esteem positively influences emotion regulation and negatively influences bullying involvement, while bullying experiences negatively impact self-esteem and social adjustment. Emotion regulation also negatively impacts bullying behavior. Furthermore, Social Emotional Learning (SEL)-based interventions have been shown to improve social-emotional competence and decrease bullying behavior in students. Conclusion: Self-esteem and emotion regulation are key protective factors in reducing bullying, and strengthening them through SEL is effective as a school-based preventive strategy. Suggestion: Future research is recommended to use a more robust design, such as a longitudinal or experimental approach, to further analyze the relationship between self-esteem, emotion regulation, and bullying behavior. Keywords: Bullying; Emotional Regulation; Self-Esteem; Social Emotional Learning. Pendahuluan: Bullying merupakan kekerasan berulang yang berdampak serius pada kesehatan mental remaja, dengan prevalensi global sekitar 30%. Self-esteem dan regulasi emosi berperan sebagai faktor risiko dan protektif, sementara pendekatan social emotional learning (SEL) berpotensi sebagai strategi pencegahan, namun integrasinya masih terbatas. Tujuan: Untuk mengidentifikasi dan mengevaluasi peran social emotional learning (SEL) dalam penguatan self-esteem dan regulasi emosi sebagai upaya pencegahan bullying. Metode: Penelitian systematic literature review dengan mengacu pada pedoman PRISMA 2020. Analisis menggunakan sintesis naratif kuantitatif dan penilaian kualitas JBI. Penelusuran literatur dilakukan melalui 4 basis data, yaitu ScienceDirect, ERIC, Google Scholar, dan PubMed, sebanyak 2,137 artikel teridentifikasi, 79 duplikat dihapus, dan 1,872 dieliminasi pada penyaringan awal. Dari 186 artikel yang diseleksi, tersisa 16 studi yang memenuhi kriteria inklusi. Hasil: Self-esteem dan regulasi emosi berhubungan signifikan dengan perilaku bullying. Self-esteem berpengaruh positif terhadap regulasi emosi dan negatif terhadap keterlibatan bullying, sementara pengalaman bullying berdampak pada penurunan harga diri dan penyesuaian sosial. Regulasi emosi juga berpengaruh negatif terhadap perilaku bullying. Selain itu, intervensi berbasis Social Emotional Learning (SEL) terbukti berdampak pada peningkatan kompetensi sosial-emosional serta penurunan perilaku bullying pada siswa. Simpulan: Self-esteem dan regulasi emosi merupakan faktor protektif utama dalam menurunkan bullying dan penguatannya melalui SEL efektif sebagai strategi preventif berbasis sekolah. Saran: Penelitian selanjutnya disarankan menggunakan desain yang lebih kuat, seperti longitudinal atau eksperimental, agar hubungan antara self-esteem, regulasi emosi, dan perilaku bullying dapat dianalisis secara lebih mendalam. Kata Kunci: Bullying; Regulasi Emosi; Self-Esteem; Social Emotional Learning.